2022
DOI: 10.3389/fbioe.2022.841298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Samples’ Surface With Complex Microscopic Geometry on 3 × 3 Mueller Matrix Measurement of Tissue Bulks

Abstract: The clinical in vivo tissue bulks’ surface is always coarse and shows a complex microscopic geometry which may affect the visual effect of polarization images and calculation of polarization parameters of the sample. To confirm whether this effect would cause identification difficulties and misjudgments on the target recognition when performed the polarization imaging based on 3 × 3 Mueller matrix measurement, cylindrical type and slope type physical models were used to study and analyze the effect of the surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As anticipated, measuring non-flat geometries, such as with whole brain specimens, is particularly challenging and may introduce artifacts into the results. While other groups have been able to image non-flat surface geometries with minimal negative effects on their results (Rodríguez-Núñez et al, 2021b;Liu et al, 2022), they used wide field imaging which may have a larger depth of field than the microscopy system used in this study. To account for the limitations of this system, further studies utilizing tissue phantoms will be undertaken to characterize how curved surfaces may influence the acquisition and reconstruction of Mueller Matrix data.…”
Section: Discussionmentioning
confidence: 99%
“…As anticipated, measuring non-flat geometries, such as with whole brain specimens, is particularly challenging and may introduce artifacts into the results. While other groups have been able to image non-flat surface geometries with minimal negative effects on their results (Rodríguez-Núñez et al, 2021b;Liu et al, 2022), they used wide field imaging which may have a larger depth of field than the microscopy system used in this study. To account for the limitations of this system, further studies utilizing tissue phantoms will be undertaken to characterize how curved surfaces may influence the acquisition and reconstruction of Mueller Matrix data.…”
Section: Discussionmentioning
confidence: 99%
“…9 Additionally, though the retardance response of fiber inclination is well understood for transmittance PLI, 1,7 for reflectance PLI systems the effects have not been thoroughly investigated yet. Similarly while surface topology has been studied previously 8,16 the effects of fibers curving out of plane and the ability of reflectance PLI to map those has yet to be investigated. A better understanding of how PLI systems respond to these microstructures would be advantageous to moving the technique away from flat sectioned samples towards in vivo three-dimensional brain imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the effects of surface topology have been studied previously by Rodriguez et al who tilted and rotated fresh calf brain samples to determine this did not diminish their ability to map the optical axis of the sample 2 and Liu et al who used a reflectance based polarmetric system to image various types of tumor samples and found that surface geometry had a minimal effect on distinguishing between tumor and healthy tissue. 27 However, the effects and quantification of fibers and tissue curving out of plane on polarization properties as a whole and the ability of backscattering PLI to map those has yet to be thoroughly investigated. A better understanding of how PLI systems respond to these different microstructural arrangements is essential to advance the technique away from flat sectioned samples towards in vivo imaging of threedimensional brain structures.…”
Section: Introductionmentioning
confidence: 99%
“…who tilted and rotated fresh calf brain samples to determine this did not diminish their ability to map the optical axis of the sample 2 and Liu et al. who used a reflectance based polarmetric system to image various types of tumor samples and found that surface geometry had a minimal effect on distinguishing between tumor and healthy tissue 27 . However, the effects and quantification of fibers and tissue curving out of plane on polarization properties as a whole and the ability of backscattering PLI to map those has yet to be thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%